2020
DOI: 10.1080/09546634.2020.1762843
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient teledermatology during the COVID-19 pandemic

Abstract: Coronavirus Disease 2019 (COVID-19) represents a global health crisis in which personal protective equipment has become increasingly limited. Dermatologists are poised to use technology, such as teledermatology, to innovate existing workflows and optimize dermatologic care. The state of Ohio has emerged as a leader in the United States with its response to the COVID-19 crisis. In response to the COVID-19 crisis, we developed a simple algorithm and strict guidelines to prioritize telemedicine specifically for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 5 publications
1
36
0
7
Order By: Relevance
“…were the most common reasons for the dermatology visits in parallel to their frequency in normal times; again not an emergency situation T A B L E 3 Physicians' opinion concerning the essentialness of the each of 902 face-to-face visits our results should be viewed as a support to the studies that have exhibited different success rates with the use of teledermatology for inpatient/outpatient dermatology services. 10,13,14 In conclusion, with the data provided by our study, we are able to prove the unnecessary patient overload during the pandemic and confirm the necessity of the substitution of face-to-face hospital visits with remote healthcare systems. The current question is about the finding the best tool/s to use in Turkey.…”
Section: Discussionsupporting
confidence: 72%
“…were the most common reasons for the dermatology visits in parallel to their frequency in normal times; again not an emergency situation T A B L E 3 Physicians' opinion concerning the essentialness of the each of 902 face-to-face visits our results should be viewed as a support to the studies that have exhibited different success rates with the use of teledermatology for inpatient/outpatient dermatology services. 10,13,14 In conclusion, with the data provided by our study, we are able to prove the unnecessary patient overload during the pandemic and confirm the necessity of the substitution of face-to-face hospital visits with remote healthcare systems. The current question is about the finding the best tool/s to use in Turkey.…”
Section: Discussionsupporting
confidence: 72%
“…During the shutdown period, patients affected by chronic skin diseases have been deprived of their regular dermatological consultations, since outpatient visits were mostly limited to urgent cases. Teledermatology services have been a useful tool to mitigate the impact of lack of faceto-face visits (19,20) even if this modality is not widely available in Italy or patients might be not familiar with it.…”
Section: Discussionmentioning
confidence: 99%
“…W ith the coronavirus disease 2019 (COVID- 19) pandemic, otolaryngologists, among other specialties, implemented telehealth strategies to adapt to physical distancing guidelines. [1][2][3][4][5][6][7][8][9] Previous studies demonstrated telehealth to be cost-effective and useful. [10][11][12][13][14] Given the perceived utility of remote care under these circumstances, policy changes have readily promoted its increased use across specialties.…”
mentioning
confidence: 99%